Between Power Plays and Interests: A Return to the Core Purpose of Evaluation - Marchand, Marie-Pier; Hurteau, Marthe (Mesure et évaluation en éducation, 2024)
The credibility given to evaluation results by stakeholders remains a significant concern for evaluators. How do stakeholders, who are interested parties, perceive the evaluation process and the credibility of the generated results? This article presents the documented perceptions of stakeholders as to the credibility of the obtained results and the overarching process. These perceptions are then compared to evaluators’ points of view. The discourses converge on several levels; however,a potential divergence is underlined in the way stakeholders and evaluators come to understand the aim of the evaluation process. The analysis thus focuses on this divergence and its implications of the evaluation process in such a way that an innovative solution is submitted, which requires, nevertheless, a repositioning of the evaluators’ relationship to the approach and to stakeholders.